Edible blue-green algae reduce the production of pro-inflammatory cytokines by inhibiting NF-κB pathway in macrophages and splenocytes - Ku, Chai Siah; Pham, Tho X.; Park, Youngki; Kim, Bohkyung; Shin, Min Sun; Kang, Insoo; Lee, Jiyoung (Biochimica et biophysica acta, 2013)
Chronic inflammation contributes to the development of pathological disorders including insulin resistance and atherosclerosis. Identification of anti-inflammatory natural products can prevent the inflammatory diseases. Anti-inflammatory effects of blue-green algae (BGA), i.e., Nostoc commune var. sphaeroides Kützing (NO) and Spirulina platensis (SP), were compared in RAW 264.7 and mouse bone marrow-derived macrophages (BMM) as well as splenocytes from apolipoprotein E knockout (apoE−/−) mice fed BGA. When macrophages pretreated with 100μg/ml NO lipid extract (NOE) or SP lipid extract (SPE) were activated by lipopolysaccharide (LPS), expression and secretion of pro-inflammatory cytokines, such as tumor necrosis factor α (TNFα), interleukin 1β (IL-1β), and IL-6, were significantly repressed. NOE and SPE also significantly repressed the expression of TNFα and IL-1β in BMM. LPS-induced secretion of IL-6 was lower in splenocytes from apoE−/− fed an atherogenic diet containing 5% NO or SP for 12weeks. In RAW 264.7 macrophages, NOE and SPE markedly decreased nuclear translocation of NF-κB. The degree of repression of pro-inflammatory gene expression by algal extracts was much stronger than that of SN50, an inhibitor of NF-κB nuclear translocation. Trichostatin A, a pan histone deacetylase inhibitor, increased basal expression of IL-1β and attenuated the repression of the gene expression by SPE. SPE significantly down-regulated mRNA abundance of 11 HDAC isoforms, consequently increasing acetylated histone 3 levels. NOE and SPE repress pro-inflammatory cytokine expression and secretion in macrophages and splenocytes via inhibition of NF-κB pathway. Histone acetylation state is likely involved in the inhibition. This study underscores natural products can exert anti-inflammatory effects by epigenetic modifications such as histone acetylation. ► Anti-inflammatory effects of edible blue-green algae in macrophages ► Inhibition of NF-κB pathway for the anti-inflammatory effects in macrophages ► Repression of IL-6 secretion from splenocytes of mice fed blue-green algae ► Role of histone deacetylases in the anti-inflammatory role of blue-green algae